The Construction, Deconstruction And Reconstruction Of Crime News: A Case Study Of The Malaysian Newspapers - Azmawati, Azman Azwan (Universiti Sains Malaysia, 2016)

(untitled)
The mass media are important agents of socialization in that they reproduce dominant (and other) social norms, beliefs, discourses, ideologies and values. Although media are said to be an educator, most of the transmission of norms, beliefs, ideologies, discourses and values happen in an unconscious fashion. (Deverux, E. 2003: p10). In essence, the media select and process facts for us. Because they do so systematically, they necessarily affect the way we interpret what they are saying. As well as informing us, the media also shape us. In order to understand fully how the process works, we need to become literate in the various languages of the media. Media literacy means more than just responding to media messages. It also means understanding how they work, how they differ from personal experience and how they differ from each other. It means learning about their dominant style and being able, when necessary, to use them (Hart, A. 1991. pg 8-9)